Decision Support System for Selection of Candidates for PASKIBRAKA Using the TOPSIS Method - Nungsiyati Nungsiyati; Sri Hartati; Deli Wahana Aprilianti (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Activities in the selection of candidates for PASKIBRAKA every year aim to find the best sons and daughters who will be assigned as heirloom flag raisers. Selection of candidates for PASKIBRAKA members is done manually, to determine the final score of each participant. The selection committee still uses paper and is separate from the assessment to one criterion with the other criteria. In the assessment process with a large number of participants it will take a long time. To simplify the assessment process, a decision support system is needed for the selection of PASKIBRAKA candidates, using the TOPSIS Method (Technique for Order Preference by Similarity to Ideal Solution). TOPSIS is one method that is easy to use to solve multi-criteria problems by taking into account the values ​​of existing criteria. Based on the results of the case example, the candidate PASKIBRAKA selection shows that the results of the experiment use the same system as the manual calculation. And the calculation of the TOPSIS Method will produce output in the form of ranking from PAKIBRAKA candidates